2020
DOI: 10.1097/olq.0000000000001161
|View full text |Cite
|
Sign up to set email alerts
|

A Secondary Mixed Methods Analysis of a Pay-it-Forward Gonorrhea/Chlamydia Testing Program Among Men Who Have Sex With Men in China

Abstract: Background Gonorrhea and chlamydia are common among Chinese men who have sex with men (MSM), but testing rates are low. We developed a pay-it-forward program where men receive a free gonorrhea/chlamydia test and can then donate toward future participants' tests. This study aims to investigate drivers of testing uptake and donation using a mixed methods approach. Methods We used a sequential explanatory design to explore drivers of testing uptake and don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 15 publications
(49 citation statements)
references
References 25 publications
1
48
0
Order By: Relevance
“…Engaging the community in vaccination services through cultivating kindness and reciprocity may also strengthen community solidarity, and increase con dence in vaccine services. 14,22 The study has several limitations. First, although our study was implemented after COVID-19 lockdowns were lifted, all sites were heavily focused on COVID-19 prevention, COVID-19 vaccination, and related COVID-19 activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Engaging the community in vaccination services through cultivating kindness and reciprocity may also strengthen community solidarity, and increase con dence in vaccine services. 14,22 The study has several limitations. First, although our study was implemented after COVID-19 lockdowns were lifted, all sites were heavily focused on COVID-19 prevention, COVID-19 vaccination, and related COVID-19 activities.…”
Section: Discussionmentioning
confidence: 99%
“…12 13 In addition, over 90% of participants donated to the rolling nance pool, 12,13 and qualitative data showed that trust in health services improved among participants in the pay-it-forward arm. 14 In this quasi-experimental pragmatic trial, we assessed the effectiveness of a pay-it-forward intervention to increase in uenza vaccination uptake at three study sites among children (aged between 6 months and 8 years) and older adults (aged 60 or above) in comparison to free vaccination and the current standard of care (user-paid vaccination) in China.…”
Section: Introductionmentioning
confidence: 99%
“…12 13 In addition, over 90% of participants donated to the rolling finance pool, 12,13 and qualitative data showed that trust in health services improved among participants in the pay-it-forward arm. 14…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Over 90% of participants donated to the rolling finance pool, and qualitative data showed that trust in health services improved among participants in the pay-it-forward arm. 15 But pay-it-forward has not been examined in increasing vaccination services uptake in community-based primary care facilities in the public sector.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation